Oxidative Cleavage of 1,3-Disubstituted Benzo[c]furans with Activated Manganese Dioxide: A Facile Preparation of 1,2-Di(het)aroylbenzenes - Sivasakthikumaran, Ramakrishnan; Nandakumar, Meganathan; Mohanakrishnan, Arasambattu K. (Synlett, 2014)
Manganese dioxide mediated oxidative cleavage of 1,3-disubstituted benzo[c]furans in dichloromethane at room temperature gave good yields of 1,2-di(het)aroylbenzenes.
Keywords: heterocycles; polycycles; diketones; ring opening; oxidation; manganese dioxide